Analisis Komparatif Implementasi Pernyataan Standar Akuntansi Keuangan (PSAK) No. 18 dan No. 24 Pada Perusahaan Daerah Air Minum (PDAM) Trunojoyo Sampang - Arief Rachman Prabaswara; nur hayati; Masluhah (Yos Soedarso Economic Journal (YEJ), 2024)
This research aims to determine the accounting treatment consisting of the concepts of recognition, measurement, recording, presentation and disclosure of pension funds and employee benefits which are applied to the accounting for pension funds and employee benefits at PDAM Trunojoyo Sampang based on Statement of Accounting Standards (PSAK) No. 18 and No. 24. This research uses qualitative research and is included in the descriptive category using a case study approach. The descriptive method, as a qualitative approach, involves an in-depth examination of a particular incident in a phenomenon. This method is characterized by analytical, classification and investigative characteristics, using techniques such as surveys, interviews and observations. Research results The accounting practice of employee benefits at PDAM Trunojoyo Sampang is in accordance with the requirements contained in PSAK 24. This involves accurate recognition of short-term employee benefits, such as salaries, director's allowances, and employee food and health benefits. And PDAM Trunojoyo Sampang's post-employment benefit program is held by DAPENMA PAMSI, fully in accordance with the current PSAK and the legal framework governing post-employment benefit programs.